Kajian Yuridis Putusan Mahkamah Agung dalam Penyelesaian Sengketa Pada Perusahaan Leasing Dengan Badan Penyelesaian Sengketa Konsumen - Azizah, Agustine (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2021)
The purpose of this study for reviewed the dispute resolution between the finance company and the consumer decided by BPSK in the case of Supreme Court Decision Number 210 K/Pdt.Sus-BPSK/2015 and examine the consideration of the Supreme Court Judge stating that BPSK is not authorized to decide case in between consumer financing companies.This research is normative descriptive who use secondary data and collecting data use literature study. Data analysis use interactive model.The result of the research indicates that the Supreme Court Decision Number 210 K/Pdt.Sus- BPSK/2015 in the case of special dispute on consumer dispute between First Indo American Leasing Branch Bandung (